Metalinguistic Play as a Methodological Approach to the Development of the Metalinguistic Function of Speech in Children - Vladimir Vukomanović Rastegorac (University of Belgrade, Teacher Education Faculty, 2021)
Some studies have unequivocally indicated the links between the early development of metalinguistic consciousness and the later success of children in the acquisition of literacy, as well as with their integration into society. However, in the context of the methodology of speech development, the multiplicity of aspects of metalinguistic consciousness has not been thoroughly examined so far. This paper attempts to fill this gap and show a possible approach to the development of the metalinguistic consciousness and the metalanguage of speech function in children. The aim of the paper is twofold: a) to provide a systematic overview of the requirements that can examine and encourage metalinguistic awareness in children and b) to present a model of crossing the metalanguage tasks with traditional forms of play, so that the work on developing the metalinguistic awareness in preschool institutions can be carried out adequately, considering the cognitive and socio-emotional characteristics of the child - through metalinguistic games.